Nucleotide diversity of Hemigrammus cf. marginatus (Characiformes, Characidae) in the upper Paraná river floodplain - doi: 10.4025/actascibiolsci.v34i3.6669 - Thiago Cintra Maniglia; Alberto José Prioli; Thais Souto Bignotto; Talge Aiex Boni; Sônia Maria Alves Pinto Prioli; Carla Simone Pavanelli (Acta Scientiarum. Biological Sciences, 2012)
Characidae is the largest and more diversified family from Characiformes and presents several classification problems, with several genera currently allocated as incertae sedis, such as the genus Hemigrammus. The upper Paraná river floodplain is an environment with high fish diversity. There is at least one species of Hemigrammus, however there are divergences among some authors about the number and the identification of the species from this genus. Therefore the goal of this study was to characterize, using a molecular approach, individuals of Hemigrammus from the upper Paraná river floodplain and to compare them with individuals from the type locality of Hemigrammus marginatus, since this is the only species distributed in this floodplain. For this, the DNA was extracted and a partial region from the mitochondrial genes ATPase 6 and ATPase 8 were amplified and sequenced. The results evidenced the existence of two species of Hemigrammus in the floodplain, although impossible to be distinguished only through morphological traits. High nucleotide diversity among individuals from the upper Paraná river in relation to those from the type locality was also observed, indicating that both species of Hemigrammus present in the upper Paraná river floodplain are not Hemigrammus marginatus.